2022
DOI: 10.1021/acs.iecr.1c04575
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous and Sandwich-like Sulfur-Doped Carbon Nanosheets as High-Performance Anodes for Sodium-Ion Batteries

Abstract: The development of high-performance carbon-based anodes for Na-ion batteries is highly desired but still remains challenging because of carbon materials with a low reversible capacity and poor cyclic performance. Herein, novel S-doped carbon nanosheets (SCNs) were prepared by a hydrothermal self-assembly process in the presence of graphene oxide (GO) as the matrix, starch as the carbon source, and dibenzyl disulfide as the sulfur source. The obtained SCNs with hierarchical pores and a sandwich-like structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Figure e,f shows the high-resolution C 1s and S 2p XPS images. CC and C–C bonding were seen in the C 1s XPS spectra at 284.1 and 285.0 eV, respectively, while C–S and CO bonding were verified at the higher binding energy levels with peak positions of 286 and 288 eV . The S 2p spectrum was separated into three peaks: two major peaks located at 163.37 and 164.64 eV correspond to S 2p 3/2 and S 2p 1/2 peaks of the covalent C–S bond of thiophene-type sulfur because of the spin–orbit coupling, and a broad peak located at 167.8 eV is assigned to the C-(SOx)-C bond. , Additionally, using CHNS analysis, it was shown that the proportion (weight %) of S in the carbon framework reduced from 9.6 for CS-1000 to 5.5 for CS-1100 and 3.25 for CS-1200, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure e,f shows the high-resolution C 1s and S 2p XPS images. CC and C–C bonding were seen in the C 1s XPS spectra at 284.1 and 285.0 eV, respectively, while C–S and CO bonding were verified at the higher binding energy levels with peak positions of 286 and 288 eV . The S 2p spectrum was separated into three peaks: two major peaks located at 163.37 and 164.64 eV correspond to S 2p 3/2 and S 2p 1/2 peaks of the covalent C–S bond of thiophene-type sulfur because of the spin–orbit coupling, and a broad peak located at 167.8 eV is assigned to the C-(SOx)-C bond. , Additionally, using CHNS analysis, it was shown that the proportion (weight %) of S in the carbon framework reduced from 9.6 for CS-1000 to 5.5 for CS-1100 and 3.25 for CS-1200, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The increase in the G-band from CS-1000 to CS-1100 with an increase in annealing temperature could be responsible for the decrease in the R CT value. The following equations, eqs and , were used to compute the ionic diffusion coefficient ( D Na+ ) for each of the three electrode materials where T stands for the absolute temperature, F stands for the Faraday constant, A stands for the electrode’s area, ω is the angular frequency, σ is the Warburg factor value, C represents the concentration of sodium ions, n stands for the number of electrons, and R stands for the gas constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized N-doped carbons prepared at four different temperatures (Scheme ) were subjected to powdered X-ray diffraction (p-XRD) analysis. Figure a presents the p-XRD patterns of NC-800, 1000, 1200, and 1400 with the presence of sharp diffraction peaks positioned at a 2θ value of 26.3° corresponding to the (002) plane of carbon and other small peaks at a 2θ value of 43° corresponding to the (100) plane of carbon . With the rise in annealing temperature from 800 to 1400 °C, the sharp rise in the (002) plane indicates the increase in the graphitic nature of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the R CT value with rise in annealation temperature may be attributed to the significant rise in graphitic domains from NC-800 to NC-1400. The ionic diffusion coefficient ( D Na+ ) was calculated for all of the four electrode materials using the following eqs and where R represents the gas constant, T stands for absolute temperature, A represents the area of the electrode, F denotes Faraday constant, n stands for the quantity of electrons, C is the Na + concentration, σ presents the value of Warburg factor, and ω represents the angular frequency.…”
Section: Resultsmentioning
confidence: 99%